Rapid Access to Ordered Mesoporous Carbons for Chemical Hydrogen Storage. Issue 41 (7th September 2021) - Jeong, Uiseok; Kim, HyeonJi; Ramesh, Sreerangappa; Dogan, Nesibe A.; Wongwilawan, Sirinapa; Kang, Sungsu; Park, Jungwon; Cho, Eun Seon; Yavuz, Cafer T.
Abstract: Ordered mesoporous carbon materials offer robust network of organized pores for energy storage and catalysis applications, but suffer from time‐consuming and intricate preparations hindering their widespread use. Here we report a new and rapid synthetic route for a N‐doped ordered mesoporous carbon structure through a preferential heating of iron oxide nanoparticles by microwaves. A nanoporous covalent organic polymer is first formed in situ covering the hard templates of assembled nanoparticles, paving the way for a long‐range order in a carbonaceous nanocomposite precursor. Upon removal of the template, a well‐defined cubic mesoporous carbon structure was revealed. The ordered mesoporous carbon was used in solid state hydrogen storage as a host scaffold for NaAlH4, where remarkable improvement in hydrogen desorption kinetics was observed. The state‐of‐the‐art lowest activation energy of dehydrogenation as a single step was attributed to their ordered pore structure and N‐doping effect. Abstract : Nitrogen‐doped ordered porous carbon was synthesized by microwave heating using Fe3 O4 nanoparticles as hard templates. The microwave‐assisted method reduces the reaction time and provides highly ordered structure with large surface area and nitrogen doping. NaAlH4 was confined into the pores of the carbon scaffold and the hydrogen sorption kinetics is improved by the synergistic effects of nanoconfinement and nitrogen doping.